Characteristics and outcomes of rhegmategenous retinal detachment in stickler syndrome at a tertiary eye care center in Saudi Arabia - Alshahrani, Saeed T. (2012)
Purpose: : to investigate the clinical findings of Stickler syndrome-associated rhegmatogenous retinal detachment (RRD) and the outcome of surgery in patients seen at the King Khaled Eye Specialist Hospital (KKESH) in Saudi Arabia.. The effect of prophylactic retinopexy on the fellow eyes is also reported. Methods: : a retrospective chart review of all patients with Stickler syndrome-associated RRD registered at KKESH during the period from 1983-2010 Results: : One-hundred and fifty patients with Stickler syndrome-associated RRD were identified out of which 11 have been reviewed so far. The age ranged from 4 to 24 years (average 13 years) and the follow up from 1 to 6 years (average 2.5 years). Six patients (55%) were males, and 4 (36%) had a previous history of RRD repair in the fellow eye. The macula was involved in 10 (90%) eyes, and the RRD was total in 7 eyes. The RRD was due to hoarse shoe retinal breaks in 9 (81%) eyes and due to giant retinal breaks in 2 (19%) eyes. Lattice degeneration was present in 8 (72%) eyes. Scleral buckle (SB) alone was performed in 1 eye only and SB combined with vitrectomy in10 (91%). The primary anatomical success rate was 91%. Five eyes (45%) had recurrent RRD within a period of 2 weeks to 8 months (average 4 months) following surgery. These were successfully repaired with repeat vitrectomy and silicone oil injection. All but one eye had their retinas completely attached at last follow up. Snellen median visual acuity improved from count fingers at 3feet (range 20/100 to hand motion) at baseline to 20/200 (range 20/40 to HM) at final follow up with 55% of eyes having better than 20/100 vision. The best visual outcome was noticed in three eyes with previous prophylactic laser to the involved eye who all presented with partial RRD and partial macular involvement. The vision in these eyes improved from a baseline Snellen acuity of 20/100-20/200 to a final acuity of ≥20/40. Six (55%) eyes underwent 360° prophylactic laser therapy in their fellow eye. Of those 2 (33.3%) progressed to RRD during follow up. Conclusions: : RRD from stickler syndrome is complex and difficult to manage with a high recurrence rate. Combined SB and vitrectomy appears to yield a higher primary success rate compared to what was previously reported. Prophylactic laser appears to protect against RRD development and to be associated with a better visual outcome after surgery should RRD occur. Larger scale prospective studies are needed to confirm these findings.